INVESTIGATION OF THERMOSTRESSED STATE OF STEEL INGOT AT TRANSPORTATION FROM FURNACE TO ROLLING MILL - V. I. Timoshpolskij; I. A. Trusova; P. E. Ratnikov; D. V. Mendelev (Литьë и металлургия)
Analytical investigation of temperature and thermostressed state of ingots at cooling is carried out and dependence of the temperature stresses level on index of surface heat-sink cooling along the perimeter of ingot is determined.